The Recycling Aluminium CNC Waste Into Gardening Tools - Othman, Muhammad Izzat Baihaqi; Yusof, Yusri (Research Progress in Mechanical and Manufacturing Engineering, 2023)
This study aims to evaluate the various methods for limiting aluminium chip disposal that can be used to reach zero waste generation. The study also considered if there would be a bigger difference between modern products made of some of the other materials, such steel, and those made of recycled aluminium. The goal of the study is to determine how to lessen the amount of CNC aluminium trash that is dumped in the junkyard in order to minimise material pollution from mechanical shops, factories, and companies. Another goal of the project is to examine the process for turning scrap CNC aluminium into recyclable goods that can benefit consumers more.